PEMBERIAN EDUKASI TENTANG BAHAYA PEWARNA SINTETIS (RHODAMIN B) SERTA DETEKSI RHODAMIN B PADA SAMPEL MAKANAN RINGAN DI KAWASAN SDN NGLAMPIR TULUNGAGUNG - Yunita Diyah Safitri (Politeknik Negeri Sriwijaya, 2021)
Synthetic dye such as Rhodamine B is generally used by textile and paper manufacturers to attract consumer interest in their products. In the last few years, the usage of Rhodamine B has also been found in food production in Indonesia. The Indonesian government has banned the usage of Rhodamine B for food production which is stated in the Regulation of the Minister of Health of the Republic of Indonesia Number: 239 / Menkes / Per / V / 1985, regarding certain dyes that are declared as hazardous materials. The usage of Rhodamine B in food production may cause indigestion, respiratory disorders, and liver poisoning, and in the long term use may cause cancer. Rhodamine B is usually found in light red-colored snacks that are often sold in the elementary school areas, especially Nglampir Elementary School. Nglampir Village is located in Bandung District, Tulungagung. People around the school areas mostly unknown about the risk of consuming synthetic dye and its effect on the human health. In this service, we gave some information to locals about the risk of consuming Rhodamin B in the food, as well as tested some snacks that are suspected of containing Rhodamine B in Nglampir Elementary School areas. We used presentation and discussion methods, also practiced of Rhodamine B tested in some suspected samples using Rhodamine B test kit. The results showed that all of the samples were negative to Rhodamin B. In the conclusion, some suspected snacks did not use Rhodamine B as its food dye.